Dual roles and potential applications of exosomes in HCV infections - Yin, Yiqian; Zhao, Yuxue; Chen, Qiaoqiao; Chen, Yiwen; Mao, Lingxiang (Frontiers in Microbiology, 2022)
The hepatitis C virus (HCV) can elicit severe liver disease (e.g., hepatitis, liver cirrhosis, hepatocellular carcinoma) and lead to high morbidity and mortality. Antibody- targeting receptor-mediated infection of HCV can limited therapeutic benefits, which suggests that the transmission of HCV infection might depend on receptor-independent mechanisms. Exosomes are membrane-enclosed vesicles (30-200 nm) originating from fusion of endosomal multivesicular bodies with the plasma membrane. A growing body of evidence suggests the pivotal role of exosomes in HCV infection. On the one hand, exosomes can transfer viral and cellular bioactive substances (e.g., nucleic acids, proteins) to the uninfected cells to expand the infection and mask these materials from immunological recognition. On the other hand, exosomes originating from some types of cells can deliver antiviral molecules or prompt the immune response to inhibit HCV infection. In addition, exosomes could be applied in the diagnosis of HCV-related disease and be evaluated as tools of drug delivery in its treatment. This review summarizes current knowledge on the dual role and potential application of exosomes in HCV infection.